Performance of P/B and P/E based value and growth strategies within industry groups : Empirical evidence from Nordic stock market - Lahti, Aleksi (My University, 2021)
The purpose of the thesis is to study the performance of P/B (P/E) based relative value and growth strategies within different industry groups. Another aim of the thesis is to examine whether the performance of P/B (P/E) based relative value and growth strategies differs between industry groups. It is also studied whether the performance of relative value (growth) strategies within industry groups differs between P/B and P/E based portfolio formation criteria. Furthermore, it is examined whether the industry group specific P/B (P/E) based relative value and growth strategies manage to gain positive alpha in the Nordic stock market when compared to a capital asset pricing model (CAPM) and Fama-French three-factor model (FF3). The research focuses on the Nordic stock market including publicly listed companies from Copenhagen, Helsinki, Iceland, Oslo, and Stockholm Stock Exchanges. The research period is 15 years from May 2005 to April 2020. Value and growth portfolios are constructed based on B/P (E/P) ratios employing a one-dimensional ranking of companies. However, unlike several previous studies, portfolios are formed by using a relative approach separately within six different industry groups. Although the mean return differences between the relative value and growth strategies are statistically insignificant within each industry group, the results still suggest that within industry groups, P/B based relative growth strategy outperforms the corresponding value strategy, and P/E based relative value strategy outperforms the corresponding growth strategy. Despite statistical insignificances, the findings also suggest that the P/B based relative growth strategy outperforms the P/E based relative growth strategy, and vice versa, the P/E based relative value strategy outperforms the P/B based relative value strategy in the Nordic stock market. However, the findings provide no consistent evidence that the performance of relative value (growth) strategies is dependent on the industry characteristics. A few portfolios manage to gain economically and statistically significant positive alpha when compared to the FF3. However, the adjusted R2 values are quite low suggesting that the FF3 may not be a robust asset pricing model in the Nordic stock market. Therefore, rather than market inefficiency, the findings suggest that the applied FF3 lacks some risk factors. The results provide updated information on the industry group specific market efficiency and the robustness of the CAPM and FF3 in the Nordic market. The findings also contain useful information to support relative valuation analyses in practice. However, the statistically insignificant but still economically considerable findings propose further research on the subject.

Tutkielman tarkoitus on tutkia P/B (P/E) -lukuun perustuvien suhteellisten arvo- ja kasvustrategioiden suoriutumista erilaisten toimialaryhmien sisällä. Tutkielman tavoitteena on myös tutkia, eroaako P/B (P/E) -pohjaisten suhteellisten arvo- ja kasvustrategioiden suoriutuminen toimialaryhmien välillä. Lisäksi tutkielma pyrkii selvittämään, eroaako suhteellisten arvo- ja kasvustrategioiden suoriutuminen P/B ja P/E -pohjaisten salkunmuodostuskriteerien välillä. Lisäksi tutkitaan, onnistuvatko toimialaryhmäkohtaiset P/B (P/E) -pohjaiset suhteelliset arvo- ja kasvustrategiat saavuttamaan positiivista alfaa Pohjoismaisilla osakemarkkinoilla verrattuna CAP- ja Fama-French kolmifaktorimalliin (FF3). Tutkimus keskittyy Pohjoismaihin sisältäen listayhtiöitä Tanskan, Suomen, Islannin, Norjan ja Ruotsin osakemarkkinoilta. Tutkimusajanjakso on 15 vuotta toukokuusta 2005 huhtikuuhun 2020. Arvo- ja kasvusalkut muodostetaan yksiulotteisesti B/P (E/P) -luvun perusteella. Toisin kuin useat aiemmat tutkimukset, portfoliot muodostetaan kuuden eri toimialaryhmän sisällä erikseen soveltaen arvostuskertoimien suhteellista vertailua. Vaikka suhteellisten arvo- ja kasvustrategioiden keskiarvotuottojen välillä ei ole tilastollisesti merkitsevää eroa yhdenkään toimialaryhmän sisällä, tulokset viittaavat kuitenkin siihen, että toimialaryhmien sisällä P/B-lukuun perustuva suhteellinen kasvustrategia performoi paremmin kuin vastaava arvostrategia, ja P/E-lukuun perustuva suhteellinen arvostrategia performoi paremmin kuin vastaava kasvustrategia. Huolimatta tilastollisesti ei-merkitsevistä eroista, tulokset viittaavat myös siihen, että P/B-lukuun perustuva suhteellinen kasvustrategia performoi paremmin kuin P/E-lukuun perustuva suhteellinen kasvustrategia, ja päinvastoin, P/E-lukuun perustuva suhteellinen arvostrategia performoi paremmin kuin P/B-lukuun perustuva suhteellinen arvostrategia Pohjoismaisilla osakemarkkinoilla. Tulokset eivät kuitenkaan viittaa johdonmukaisesti siihen, että suhteellisten arvo- tai kasvustrategioiden suoriutuminen olisi riippuvainen toimialan ominaisuuksista. Muutama portfolio onnistuu saavuttamaan taloudellisesti ja tilastollisesti merkitsevää positiivista alfaa verrattuna FF3-malliin. Regressioiden korjatut selitysasteet ovat kuitenkin suhteellisen matalia viitaten siihen, että FF3-malli ei välttämättä ole toimiva hinnoittelumalli Pohjoismaisilla osakemarkkinoilla. Siksi markkinatehottomuuden sijaan tulokset viittaavatkin enemmän siihen, että FF3-mallista puuttuu riskitekijöitä. Tulokset tarjoavat ajantasaista tietoa toimialaryhmäkohtaisesta markkinatehokkuudesta sekä CAP- ja FF3-mallin toimivuudesta Pohjoismaissa. Tulokset sisältävät myös hyödyllistä tietoa käytännön arvostusanalyysien tueksi. Tilastollisesti ei-merkitsevät mutta silti taloudellisesti huomattavat tulokset kannustavat kuitenkin aiheen lisätutkimuksiin.
Keywords: Value strategies, growth strategies, valuation multiples